Art in Belgium : Cyclic Identity : still life - environment - still life. - Ho, Oscar; Hoet, Jan; Patten, Christopher; So, James Y C; Van Duyse-Adam, Gaston; Van Mulders, Wim; Vande Veire, Frank; Exhibition. Art in Belgium : Cyclic Identity. Hong Kong. Arts Centre Hong Kong. Museum van Hedendaagse Kunst Gent. 1993-06-18. 1993-07-11 (Gent Hong Kong : Hong Kong Arts Centre Hong Kong Museum van Hedendaagse Kunst Gent, 1993)
Alechinsky, Pierre ; Van Anderlecht, Englebert ; Appel, Karel ; Bacon, Francis ; De Braekeleer, Henri ; Broodthaers, Marcel ; Brusselmans, Jean ; D'Haese, Roel ; d'O, Honoré ; Ensor, James ; Fabre, Jan ; Fabro, Luciano ; François, Michel ; Hockney, David ; Jorn, Asger ; De Keyser, Raoul ; Kokoschka, Oskar ; Lohaus, Bernd ; Magritte, René ; Mellery, Xavier ; Meunier, Constantin ; Minne, George ; Nauman, Bruce ; Panamarenko ; Permeke, Constant ; Raveel, Roger ; Rouault, Georges ; Spalletti, Ettore ; Spilliaert, Léon ; Tuymans, Luc ; Warhol, Andy ; Wenda, Gu ; Xu Bing
biog. per kunstenaar p. 119-135
publ. SMAK : zie kast leeszaal
Chinees
Engels
boek
Keywords: België